Target Population of Environment (TPE) modelling as a synergy between Big Data Platform (BDP) and Excellence in Breeding (EiB) platforms - CGIAR Platform for Big Data in Agriculture (2020)
A tool has been developed that offers a crop modeling framework that provides support for environment classification (TPE) and crop trait analysis. The tool has been developed and tested providing promising results.